2014
DOI: 10.1016/j.diabet.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and low-grade systemic inflammation as markers of subclinical organ damage in type 2 diabetes

Abstract: SummaryAim:The aim of this study was to explore associations between abdominal obesity, inflammatory markers, and subclinical organ damage in 740 patients with type 2 diabetes. Methods:Waist circumference (WC) and sagittal abdominal diameter (SAD) was measured. Blood samples were analyzed for; C-reactive protein (CRP) and IL-6. Carotid intima-media thickness (IMT) was evaluated by ultrasonography. Aortic pulse wave velocity (PWV) was measured with applanation tonometry. Results:Abdominal obesity measured as SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…Laboratory inflammation markers have been used as predictive tools for atherosclerosis in patients with type 2 DM (36,(40)(41)(42)(43). In our study, we found no association between the inflammation markers hs-PCR and fibrinogen with subclinical atherosclerosis in patients with type 1 DM.…”
Section: Discussioncontrasting
confidence: 49%
“…Laboratory inflammation markers have been used as predictive tools for atherosclerosis in patients with type 2 DM (36,(40)(41)(42)(43). In our study, we found no association between the inflammation markers hs-PCR and fibrinogen with subclinical atherosclerosis in patients with type 1 DM.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, both WC and sagittal abdominal diameter (SAD) are associated with subclinical organ damage such as PWV and carotid intima-media thickness and provided information on inflammation, atherosclerosis and arterial stiffness in type 2 diabetic patients [23]. However, it has also been reported that SAD was more independent in predicting arterial stiffness over time, compared with WC, in middle-aged men and women with type 2 diabetes [24], Recently , it has been demonstrated that neck circumference is associated with an increased PWV in hypertensive adults, independent of other metabolic risk factors [25].…”
Section: Discussionmentioning
confidence: 99%
“…45 Serum 8-hydroxy 20-deoxy-guanosine (8-OhdG), for example, a known sensitive marker of oxidative DNA damage and of total systemic oxidative stress in vivo, has been shown to be positively correlated with BMI in people with Type 2 diabetes mellitus. 46 Adipose tissue produces bioactive substances called adipokines, which induce the production of reactive oxygen species by a combination of mechanisms including mitochondrial and peroxisomal oxidation of fatty acids and overconsumption of oxygen, 43,44 thereby initiate a process of oxidative stress 43,44 Recent studies have highlighted the role of increased abdominal fat mass as a key driver of inflammation in Type 2 diabetes, 47 a state closely associated with increased oxidative stress 43,44 and macrovascular disease. 47 Chronic inflammation induces changes in metabolic pathways and is believed to play a significant role in the progression from obesity to Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…46 Adipose tissue produces bioactive substances called adipokines, which induce the production of reactive oxygen species by a combination of mechanisms including mitochondrial and peroxisomal oxidation of fatty acids and overconsumption of oxygen, 43,44 thereby initiate a process of oxidative stress 43,44 Recent studies have highlighted the role of increased abdominal fat mass as a key driver of inflammation in Type 2 diabetes, 47 a state closely associated with increased oxidative stress 43,44 and macrovascular disease. 47 Chronic inflammation induces changes in metabolic pathways and is believed to play a significant role in the progression from obesity to Type 2 diabetes. 48,49 Despite the lack of any direct association between BMI and MPOD observed herein, it is plausible to suggest that 1) more refined methods of body fat assessment such as bioelectrical impedance analysis 50 and waist-to-height ratio 41 might reveal an association that could explain the lower MPOD values observed in Type 2 diabetic subjects here and 2) that the combined effect of increased competition for lutein/zeaxanthin deposition and increased inflammation and oxidative stress levels in association with higher BMI/body fat, might explain, at least in part, the lower MPOD levels observed in the Type 2 diabetes group.…”
Section: Discussionmentioning
confidence: 99%